Oral pyogenic granuloma: An 18-year retrospective clinicopathological and immunohistochemical study - Ribeiro, Jaqueline L. [UNESP]; Moraes, Renata M. [UNESP]; Carvalho, Bruna F. C. [UNESP]; Nascimento, Anderson O. [UNESP]; Milhan, Noala V. M. [UNESP]; Anbinder, Ana Lia [UNESP] (Wiley, 2021)
Background: Pyogenic granuloma (PG) is a lesion characterized by the proliferation of blood vessels, commonly affecting the skin and the mouth. We aimed to compare clinical, microscopic, and immunohistochemical features of the two types of oral PG: lobular capillary hemangioma (LCH) and non-LCH (NLCH). Methods: Epidemiological and clinical data from 2000 to 2018 were collected from the archives of our institution, and histopathological sections of PG were reviewed. Immunohistochemical analyses (CD34, D2-40, SMA, mast cell, and Ki-67) were performed in 34 cases. Results: Sixty-two LCH and 107 non-LCH samples were included. The mean (±SD) age of the patients was 38.59 ± 16.96 years; 55.62% were female; 39.64% of cases occurred in the gingiva, 44% of the nodules were pedunculated, and 13.02% of patients reported a history of trauma. NLCH was more prevalent among older patients than LCH. The most prevalent site of LCH was the lips, while NLCH occurred more in the gingiva (P < 0.05). Epithelial atrophy, microvessels, SMA-positive areas, and Ki-67-positive nuclei were more prevalent in LCH (P < 0.05). Conclusions: PG accounted for 2.25% of lesions archived in the pathology service and most cases were NLCH. LCH and NLCH exhibited clinicopathological differences in terms of age, site, epithelial atrophy, vascularization, and proliferation rate.